Explicitly Pressing Send: Impact of Sexting on Relationship Satisfaction. Issue 3 (26th May 2016) - Currin, Joseph M.; Jayne, Christopher N.; Hammer, Tonya R.; Brim, Tara; Hubach, Randolph D.
ABSTRACT: Given that few researchers have addressed sexting among adult samples, we sought to evaluate the prevalence of adults who sext, their sexting behaviors, and how it impacted relationship satisfaction. Analyses on the sample (N = 1171) revealed that heterosexual women are negatively impacted if they do not reciprocate a sext message; yet nonheterosexual women, and men in general, are not negatively impacted. This finding can be best understood within the framework of relational cultural theory (RCT). Implications for future research and for the practice of mental health providers are discussed.